2018
DOI: 10.1002/ptr.6229
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of faecal biomarkers in inflammatory bowel disease patients treated with oral mastiha (Pistacia lentiscus) supplement: A double‐blind and placebo‐controlled randomised trial

Abstract: Funding information ENOSI MASTIHOPARAGWGWN CHIOUThere is a keen research upon the effects of nutraceuticals on inflammatory bowel disease. The purpose of this study was to explore the effect of mastiha supplement, rich in bioactive nutraceuticals, in active inflammatory bowel disease. This is a randomised, double-blind, placebo-controlled clinical trial. Α total of 60 inflammatory bowel disease patients were enrolled and randomly allocated to mastiha (2.8 g/day) or placebo groups for 3 months adjunct to stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Another interesting result of the present study was the significant reduction in the ratios of oxLDL/LDL and oxLDL/HDL in the PL arm compared with the placebo arm. A decrease in feacal lysozyme in the PL arm has been reported in the study of Papada and coworkers [ 29 ], and this parallels the decrease in the oxLDL/LDL and oxLDL/HDL ratios. Herein, when changes in oxidative stress were assessed separately for CD and UC patients, significant changes were reported for patients with CD, showing possibly a most promising response to this antioxidant supplement in CD compared with UC.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Another interesting result of the present study was the significant reduction in the ratios of oxLDL/LDL and oxLDL/HDL in the PL arm compared with the placebo arm. A decrease in feacal lysozyme in the PL arm has been reported in the study of Papada and coworkers [ 29 ], and this parallels the decrease in the oxLDL/LDL and oxLDL/HDL ratios. Herein, when changes in oxidative stress were assessed separately for CD and UC patients, significant changes were reported for patients with CD, showing possibly a most promising response to this antioxidant supplement in CD compared with UC.…”
Section: Discussionsupporting
confidence: 69%
“…In previous research, it has been reported that a 3-month intervention with a supplement containing the natural resinous product of Pistacia lentiscus (the supplement herein given as PL), adjunctive to stable medical treatment, regulated faecal biomarkers and improved quality of life in active IBD patients compared with a placebo [ 29 ]. Herein, the aim was to explore the effects of this intervention on biomarkers of oxidative stress in active IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Besides other minor excipients, the main ingredients of a novel phytoformula, (DOGDG-121, Refl umed, named, Italy) are chios masthia and banana. The healing properties of chios masthia against ulcer and gastritis date back in the middle 1980's [9,10] and a more recent study [11][12][13][14][15][16][17], suggested that arabinogalactan-proteins (AGP's) isolated by mastic could display some moderate anti-H.pylori activity, given his reported bactericidal activity in vitro [12].…”
Section: Introductionmentioning
confidence: 99%
“…As for its anti-infl ammatory gastrointestinal properties, already in 2007, Kaliora et al [14,15], demonstrated that mastic administration in patients with active Crohn's disease (CD) signifi cantly reduced the CD activity index, plasma interleukin-6 and C-reactive protein levels while also recovering a normal total antioxidant potential. A properly done double-blind, placebo-controlled clinical study in this setting has been very recently published [16][17][18][19][20][21][22]. A minor biological ingredient of DOGDG-121, is a fl avonoid-rich banana (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation